Applying Clockwise And Counterclockwise Torque Directions In Pinch Grips : A Descriptive Study - Poh, Kiat Ng; Ka, Xuan Chai; Shiong, Lung Leh; Meng, Chauw Bee; Qiao, Hui Boon; Saptari, Adi (Trans Tech Publications, 2014)
-